Gas metal arc-weld joint
By adding nitrogen to the weld metal through controlled solid wire and shield gas compositions, the welding of high-Mn steel achieves enhanced strength and cryogenic toughness, overcoming previous challenges with high-temperature cracking and construction complexity.
Patent Information
- Application Number
- JP2023167497
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Existing welding techniques for high-Mn steel struggle to achieve welds with strength comparable to the base material, while also facing challenges with high-temperature cracking and complex welding construction management.
Incorporating nitrogen (N) into the weld metal by using solid wires with controlled N content and specific shield gas compositions, which enhances the strength of the weld metal and suppresses high-temperature cracking without requiring fine adjustments to welding conditions.
The approach results in weld joints with significantly improved yield stress and tensile strength, along with excellent cryogenic impact toughness, effectively addressing the limitations of previous methods.
Smart Images

Figure 2025057765000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas metal arc welded joint of a steel material obtained by forming a weld metal using a shielding gas and a solid wire, and in particular to a gas metal arc welded joint of a high Mn-containing austenitic steel material used in an extremely low temperature environment. [Background technology]
[0002] In recent years, environmental regulations have become stricter. Liquefied natural gas (hereinafter, also referred to as LNG) is said to be a clean fuel that does not generate air pollutants such as sulfides and sulfur oxides because it does not contain sulfur, and the demand for LNG is increasing. For the transportation or storage of LNG, the containers (tanks) that transport or store LNG are required to maintain excellent cryogenic impact toughness at temperatures below -162°C, which is the liquefaction temperature of LNG.
[0003] Due to the need to maintain this excellent cryogenic impact toughness, aluminum alloys, 9% Ni steel, austenitic stainless steel, etc. have traditionally been used as materials for containers (tanks) and the like.
[0004] However, aluminum alloys have low tensile strength, so the plate thickness of the structure must be designed to be large, and they have problems with poor weldability. In addition, 9% Ni steel requires the use of expensive Ni-based materials as welding materials, which is economically disadvantageous. In addition, austenitic stainless steels have problems with being expensive and having low base metal strength.
[0005] In view of these problems, the use of high-Mn steel containing 10 to 35 mass% Mn (hereinafter also referred to as "high Mn steel") has recently been considered as a material for containers for transporting or storing LNG. High Mn steel has an austenitic metal structure even at extremely low temperatures, does not suffer from brittle fracture, and has a higher strength than austenitic stainless steel. However, although the strength of the high Mn steel base material is improved by work hardening caused by rolling, the strength of the welded part is lower than that of the base material because it is not affected by work hardening caused by rolling, and the inherent strength of the high Mn steel cannot be fully utilized. Therefore, there has been a demand for the development of welding materials and welding techniques that can achieve welded parts with strength equivalent to that of the high Mn steel base material.
[0006] For example, Patent Document 1 discloses a method for making the strength and cryogenic impact toughness of a weld satisfy specified values by adjusting the chemical composition of a welding material (solid wire) and welding conditions based on the chemical composition of a high-Mn steel material and controlling the dilution rate of the steel material in the weld metal. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6978613 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the technology described in Patent Document 1, it is necessary to select welding materials suited to high-Mn steel materials, but when the cost and process of manufacturing welding materials are taken into consideration, it is difficult to design and manufacture welding materials suited to steel materials each time. In addition, there is a problem that welding construction management becomes complicated because welding conditions need to be controlled in detail.
[0009] An object of the present invention is to solve the above problems and to provide a gas metal arc welded joint of a high Mn steel that has high strength and excellent cryogenic toughness easily, without requiring detailed adjustment of the components of the welding wire or adjustment of the welding conditions. [Means for solving the problem]
[0010] In order to achieve the above object, the present inventors have thoroughly studied the effects of various elements on the properties of weld metal parts, and have found that nitrogen (N) is a particularly effective element that can be added to a weld metal from a source other than the base metal and welding material (solid wire) and contributes to improving strength. They have also found that increasing the N content in the weld metal has the effect of narrowing the solid-liquid coexistence temperature range, and also has the effect of suppressing hot cracking that occurs in the weld metal part.
[0011] Furthermore, it was discovered that by setting the N content of the solid wire to 0.400 mass% or less, N can be stably dissolved in the weld metal not from the nitrogen gas contained in the shielding gas but from the N in the solid wire.
[0012] The present invention was completed based on these findings and through further investigation, and the gist of the present invention is as follows. [1] A gas metal arc welded joint of steel material formed by forming a weld metal using a shielding gas and a solid wire, The steel material is a high Mn-containing austenitic steel, The chemical composition of the steel material is, in mass%, C: 0.10%~0.70%, Si: 0.05% to 1.00%, Mn: 18.0% to 30.0%, P:0.030% or less, S: 0.007% or less, Al: 0.010%~0.070%, Cr: 2.50%~7.00%, N: 0.0050%~0.0500%, O (oxygen): 0.0050% or less and the balance being Fe and unavoidable impurities, The chemical composition of the weld metal is, in mass%, C: 0.15%~0.80%, Si: 0.10% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Al: 0.001%~0.100%, Cr: 0.4%~5.5%, Mo: 0.01% to 3.50%, Ni: 0.01% to 10.00%, N: 0.0200%~0.1500% The balance is Fe and unavoidable impurities. 1. A gas metal arc welded joint comprising: [2] In the above [1], the chemical composition of the steel material further comprises, in mass%, Mo: 0.01% to 2.00%, V: 0.01%~2.00%, W: 0.01% to 2.00%, Ni: 0.01%~4.00%, REM: 0.0010%~0.0200% and B: 0.0003% to 0.0030% Contains one or more of the following: 1. A gas metal arc welded joint comprising: [3] In the above [1] or [2], the chemical composition of the weld metal further comprises, in mass%, V: 0.01%~1.00%, Ti: 0.010% to 1.000%, Nb: 0.010%~1.000%, W: 0.01% to 1.00%, Cu: 0.01% to 1.00% and B: 0.0015% or less Contains one or more of the following: 1. A gas metal arc welded joint comprising: [4] A gas metal arc welded joint according to any one of the above [1] to [3], characterized in that the shielding gas is any one of the gases [A] or [B] below. [A] A gas containing 1.0% or more but less than 30.0% nitrogen gas by volume, with the remainder being carbon dioxide gas and unavoidable impurities. [B] A gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas and 56.0% or more and less than 79.2% Ar gas, with the remainder being carbon dioxide gas and unavoidable impurities. [5] In any one of [1] to [4] above, the N content of the solid wire is 0.4000% or less, by mass percent. [6] In any one of the above [1] to [5], the yield stress (0.2% proof stress) of the weld metal is 400 MPa or more, the tensile strength is 600 MPa or more, and the Charpy impact absorption energy ( v E -196 ) is 28 J or more. Effect of the Invention
[0013] According to the present invention, it is possible to easily manufacture a welded joint for high-Mn steel used in an extremely low-temperature environment, which can further improve the strength of the weld metal and further suppress the occurrence of hot cracking, and thus provides a significant industrial effect. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic diagram showing an example of a groove shape in a gas metal arc welded joint of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a test piece sampling position for a Charpy impact test. [Diagram 3] FIG. 1 is a graph showing the change in 0.2% proof stress versus the N content in the weld metal resulting from the change in the nitrogen gas content. [Figure 4] FIG. 1 is a graph showing the change in tensile strength relative to the N content in the weld metal accompanying the change in nitrogen gas content. [Diagram 5]FIG. 1 is a graph showing the change in 0.2% proof stress versus the N content in the weld metal resulting from the change in the N content in the wire. [Figure 6] FIG. 1 is a graph showing the change in tensile strength relative to the N content in the weld metal accompanying the change in the N content of the wire. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] As described above, the present invention is a welded joint for high Mn steel used in an extremely low temperature environment, and is a gas metal arc welded joint that can further improve the strength of the weld metal and further suppress the occurrence of hot cracking without changing the base metal or welding material. That is, the welded joint of the present invention is a welded joint produced by gas metal arc welding in accordance with the provisions of JIS Z 3001-7 (excluding the type of shielding gas). Furthermore, in a tensile test of the welded metal produced in accordance with JIS Z 3111, the yield stress and tensile strength at room temperature are improved by an average of 10 MPa or more at a test temperature of -196°C for the welded metal of a welded joint produced in accordance with JIS Z 3128. v E -196 It has excellent cryogenic impact toughness with a cryogenic impact strength of 28J or more, and is free from high temperature cracking.
[0016] [High Mn steel (high Mn-containing austenitic steel)] First, the steel material to be the base material will be described. Any steel material may be used as long as it is a high Mn-containing austenitic steel. In the present invention, the "high Mn content" of the high Mn-containing austenitic steel means that the Mn content in the steel composition is 18.0% to 30.0% by mass. The austenitic steel of the high Mn-containing austenitic steel means a steel material whose base phase (metal structure) is an austenitic phase. That is, when the crystal structure of the steel material is a body-centered cubic structure (bcc), the steel material is not suitable for use in a low-temperature environment because it may cause brittle fracture in a low-temperature environment. Here, when assuming use in a low-temperature environment, it is essential that the base phase of the metal structure of the steel material is an austenitic structure whose crystal structure is a face-centered cubic structure (fcc). The "base phase is an austenitic phase" means that the austenitic phase is 90% or more in area ratio. The remainder other than the austenite phase is a ferrite phase or a martensite phase, or precipitates such as carbides, etc. More preferably, the austenite phase is 95% or more, and even more preferably 100%.
[0017] [Basic composition of steel] The chemical composition of the steel material according to the present invention will now be described. In this specification, "%" in "chemical composition" means "mass %". The steel material used in the present invention is a high Mn steel material containing 18.0% to 30.0% of Mn as described above, and other basic compositions are as follows: C: 0.10% to 0.70%, Si: 0.05% to 1.00%, P: 0.030% or less, S: 0.007% or less, Al: 0.010% to 0.070%, Cr: 2.50% to 7.00%, N: 0.0050% to 0.0500%, O (oxygen): 0.0050% or less. The remainder is a high Mn steel having a chemical composition consisting of Fe, arbitrarily selected compositions, and unavoidable impurities. The reasons for limiting the chemical composition are as follows.
[0018] [C:0.10%~0.70%] C is an inexpensive and important element that stabilizes the austenite phase and improves the cryogenic impact toughness. In order to obtain such an effect, the C content is set to 0.10% or more. Preferably, it is set to 0.20% or more, more preferably, it is set to 0.25% or more, even more preferably, it is set to 0.30% or more, and most preferably, it is set to 0.35% or more. On the other hand, if the C content exceeds 0.70%, Cr carbides are excessively generated, and the cryogenic impact toughness is reduced. For this reason, the C content is set to 0.70% or less. Preferably, it is set to 0.65% or less, more preferably, it is set to 0.63% or less, even more preferably, it is set to 0.61% or less, and most preferably, it is set to 0.60% or less.
[0019] [Si: 0.05%~1.00%] Si acts as a deoxidizer and is an element that dissolves in steel and contributes to increasing the strength of steel material by solid solution strengthening. In order to obtain such an effect, the Si content is set to 0.05% or more. It is preferably 0.07% or more, more preferably 0.10% or more, even more preferably 0.15%, and most preferably 0.20% or more. On the other hand, if it is contained in excess of 1.00%, the weldability decreases. For this reason, the Si content is set to 1.00% or less. It is preferably 0.80% or less, more preferably 0.70% or less, even more preferably 0.65% or less, and most preferably 0.60% or less.
[0020] [Mn: 18.0%~30.0%] Mn is a relatively inexpensive element that has the effect of stabilizing the austenite phase, and is an important element for achieving both high strength and excellent cryogenic impact toughness. In order to obtain such an effect, it is necessary to include 18.0% or more. Therefore, the Mn content is set to 18.0% or more. It is preferably 20.0% or more, more preferably 22.0% or more, and even more preferably 24.0% or more. On the other hand, even if it is included in more than 30.0%, the effect of improving the cryogenic impact toughness is saturated, and an effect commensurate with the content cannot be expected, which is economically disadvantageous. In addition, if it is included in a large amount exceeding 30.0%, it will cause a decrease in cuttability, promote Mn segregation, and promote the occurrence of stress corrosion cracking. Therefore, the Mn content is set to 30.0% or less. It is preferably 29.0% or less, more preferably 28.5% or less, and even more preferably 28.0% or less.
[0021] [P:0.030% or less] P is an element that segregates to grain boundaries as an impurity and becomes the initiation point of stress corrosion cracking. In the present invention, it is desirable to reduce the P content as much as possible, but it is acceptable if it is 0.030% or less. Therefore, the P content is 0.030% or less. It is preferably 0.028% or less, more preferably 0.024% or less, even more preferably 0.020% or less, and most preferably 0.015% or less. On the other hand, in order to extremely reduce the P content to less than 0.002%, a long refining time is required, and the refining cost rises. Therefore, from an economical point of view, the P content is preferably 0.002% or more.
[0022] [S:0.007% or less] S exists as sulfide-based inclusions in steel, and reduces the ductility and cryogenic impact toughness of steel and weld metal. For this reason, it is desirable to reduce S as much as possible, but 0.007% or less is acceptable. Therefore, the S content is set to 0.007% or less. It is preferably set to 0.005% or less, and more preferably set to 0.004% or less. On the other hand, in order to extremely reduce S to less than 0.0005%, refining for a long period of time is required, and refining costs rise. For this reason, from the viewpoint of economy, the S content is preferably set to 0.0005% or more.
[0023] [Al: 0.010%~0.070%] Al acts as a deoxidizer and is the most commonly used element in the molten steel deoxidation process for steel materials. To obtain such an effect, the Al content is set to 0.010% or more. It is preferably set to 0.020% or more, and more preferably set to 0.030% or more. On the other hand, if the Al content exceeds 0.070%, Al is mixed into the weld metal during welding, reducing the toughness of the weld metal. For this reason, the Al content is set to 0.070% or less. It is preferably set to 0.060% or less, and more preferably set to 0.050% or less.
[0024] [Cr:2.50%~7.00%] Cr is an element that stabilizes the austenite phase and effectively contributes to improving the cryogenic impact toughness and the strength of the steel material. It is also an effective element for forming a fine crystal region. In order to obtain such an effect, the Cr content is set to 2.50% or more. It is preferably 3.00% or more, more preferably 3.30% or more, even more preferably 3.50% or more, and most preferably 4.00% or more. On the other hand, if the Cr content exceeds 7.00%, Cr carbides are generated, and the cryogenic impact toughness and stress corrosion cracking resistance are reduced. For this reason, the Cr content is set to 7.00% or less. It is preferably 6.80% or less, more preferably 6.50% or less, and even more preferably 6.00% or less.
[0025] [N:0.0050%~0.0500%] N is an element that has the effect of stabilizing the austenite phase, and effectively contributes to improving the cryogenic impact toughness. In order to obtain such an effect, the N content is set to 0.0050% or more. It is preferably 0.0060% or more, more preferably 0.0070% or more, and even more preferably 0.0080% or more. On the other hand, if it is contained in excess of 0.0500%, the nitrides or carbonitrides will coarsen during the steel manufacturing process, and the cryogenic impact toughness will decrease. For this reason, the N content is set to 0.0500% or less. It is preferably 0.0450% or less, more preferably 0.0400% or less, and even more preferably 0.0350% or less.
[0026] [O (oxygen): 0.0050% or less] O (oxygen) exists as oxide-based inclusions in steel and reduces the cryogenic impact toughness of steel. For this reason, it is preferable to reduce O (oxygen) as much as possible, but 0.0050% or less is acceptable. For this reason, the O (oxygen) content is set to 0.0050% or less. It is preferably set to 0.0045% or less, and more preferably set to 0.0040% or less. On the other hand, in order to extremely reduce O (oxygen) to less than 0.0005%, a long refining time is required, and the refining cost rises. For this reason, from the viewpoint of economy, O (oxygen) is preferably set to 0.0005% or more. It is more preferably set to 0.0006% or more.
[0027] [Optional composition of steel] The above-mentioned chemical composition is the preferred basic composition of high Mn steel, but in addition to this basic composition, the following optional compositions may be contained as necessary: Mo: 0.01%-2.00%, V: 0.01%-2.00%, W: 0.01%-2.00%, Ni: 0.01%-4.00%, REM: 0.0010%-0.0200%, and B: 0.0003%-0.0030%. The reasons for limiting each composition are as follows.
[0028] [Mo, V and W: 0.01% to 2.00%] Mo, V and W are elements that contribute to the stabilization of the austenite phase, and also contribute to improving the strength and cryogenic impact toughness of the steel material, and one or more of them can be selected and contained as necessary. In order to obtain such effects, it is preferable that the content of Mo, V and W is 0.01% or more. On the other hand, if the content of Mo, V and W exceeds 2.00%, the amount of coarse carbonitride increases, which becomes the starting point of fracture, and the cryogenic impact toughness decreases. Therefore, when Mo, V and W are contained, it is preferable that the content is 2.00% or less. More preferably, the content of Mo, V and W is 1.70% or less, and even more preferably, it is 1.50% or less.
[0029] [Ni:0.01%~4.00%] Ni is an element that contributes to stabilizing the austenite phase and strengthening the austenite grain boundaries, and also contributes to improving the cryogenic impact toughness of steel materials. In order to obtain such effects, the Ni content is preferably 0.01% or more. More preferably, it is 0.10% or more, and even more preferably, it is 0.20% or more. On the other hand, Ni is an expensive element, and a content exceeding 4.00% is economically disadvantageous. Therefore, the Ni content is preferably 4.00% or less. More preferably, it is 3.75% or less, and even more preferably, it is 3.50% or less.
[0030] [REM:0.0010%~0.0200%] REM is a rare earth element such as Sc, Y, La, or Ce, and has the effect of improving the toughness of steel material, as well as ductility and resistance to sulfide stress corrosion cracking, through controlling the morphology of inclusions. In order to obtain such an effect, the REM content is preferably 0.0010% or more, and more preferably 0.0015% or more. On the other hand, if it is contained in excess of 0.0200%, the amount of nonmetallic inclusions increases, and the toughness, ductility, and resistance to sulfide stress cracking may decrease. For this reason, the REM content is preferably 0.0200% or less, and more preferably 0.0180% or less.
[0031] [B:0.0003%~0.0030%] B is an element that segregates at grain boundaries and contributes to improving the toughness of steel. To obtain such an effect, the B content is preferably 0.0003% or more, and more preferably 0.0008% or more. On the other hand, if the B content exceeds 0.0030%, the amount of coarse nitrides and carbides increases, and the toughness may decrease. For this reason, the B content is preferably 0.0030% or less, and more preferably 0.0018% or less.
[0032] [Remainder of steel composition] The remaining composition other than the above-mentioned chemical composition is composed of Fe and inevitable impurities. Incidentally, examples of inevitable impurities include Ca, Mg, Ti, Nb, and Cu, and a total of 0.05% or less is acceptable. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, elements other than these may be contained, and such embodiments are also included in the technical scope of the present invention.
[0033] [Manufacturing method of high Mn steel] Furthermore, a preferred method for producing the high Mn steel used in the present invention will be described. Note that a manufacturing method other than the method described below may be used as long as it can produce an equivalent high Mn steel, and the manufacturing method is not limited to the following method.
[0034] Molten steel having the above-mentioned steel composition is produced by a conventional melting method such as a converter or an electric furnace, and then produced into a steel material such as a slab having a predetermined size by a conventional casting method such as a continuous casting method or an ingot casting-blooming rolling method. In addition, secondary refining using a vacuum degassing furnace or the like may be performed during the production.
[0035] The obtained steel material is further heated, hot rolled and then cooled to obtain a steel material of a predetermined size. Note that, by heating at a heating temperature in the range of 1100°C to 1300°C, completing the hot rolling at a finish rolling end temperature of 790°C to 980°C, and immediately cooling, etc., a steel material with excellent cryogenic impact toughness can be obtained. In addition, in order to adjust the steel material properties, a heat treatment such as annealing treatment may be further performed.
[0036] Next, preferred mechanical properties of the high Mn steel used in the present invention will be described. The high strength steel for cryogenic use having the above-mentioned steel composition has a plate thickness of, for example, 5 mm to 102 mm, a room temperature yield stress (0.2% proof stress) of 400 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is preferably 28 J or more. Furthermore, the room temperature tensile strength is preferably 660 MPa or more, and more preferably 800 MPa or more.
[0037] [Basic composition of weld metal] In the present invention, the above-mentioned high Mn steels are welded together to form a weld metal part made of a single layer or multiple layers of weld metal by gas metal arc welding.
[0038] The basic composition of the weld metal according to the present invention is as follows: C: 0.15%-0.80%, Si: 0.10%-1.00%, Mn: 17.0%-30.0%, P: 0.030% or less, S: 0.030% or less, Al: 0.001%-0.100%, Cr: 0.4%-5.5%, Mo: 0.01%-3.50%, Ni: 0.01%-10.00%, N: 0.0200%-0.1500%, with the balance being Fe, an arbitrary selected composition, and unavoidable impurities. The reasons for limiting the chemical composition are as follows.
[0039] [C:0.15%~0.80%] C is an element that has the effect of increasing the strength of the weld metal by solid solution strengthening, and C stabilizes the austenite phase and improves the cryogenic impact toughness of the weld metal. In order to obtain such an effect, C needs to be contained at 0.15% or more. Therefore, the C content is set to 0.15% or more. Preferably, it is 0.20% or more, more preferably, it is 0.25% or more, and even more preferably, it is 0.28% or less. On the other hand, if it is contained at more than 0.80%, carbides are precipitated, the cryogenic impact toughness is reduced, and further, hot cracking during welding is easily caused. Therefore, the C content is set to 0.80% or less. Preferably, it is 0.75% or less, more preferably, it is 0.70% or less, even more preferably, it is 0.65% or less, and most preferably, it is 0.63% or less.
[0040] [Si:0.10%~1.00%] Si acts as a deoxidizer, increases the yield of Mn, increases the viscosity of the molten metal, and has the effect of stably maintaining the bead shape. In order to obtain such an effect, a content of 0.10% or more is required. Therefore, the Si content is set to 0.10% or more. It is preferably 0.15% or more, more preferably 0.20% or more, even more preferably 0.25% or more, and most preferably 0.28% or more. On the other hand, if it is contained in excess of 1.00%, it reduces the cryogenic impact toughness of the weld metal. In addition, Si segregates during solidification, generates a liquid phase at the solidification cell interface, and reduces the hot cracking resistance. Therefore, the Si content is set to 1.00% or less. It is preferably 0.80% or less, more preferably 0.75% or less, and even more preferably 0.70% or less.
[0041] [Mn: 17.0%~30.0%] Mn is an inexpensive element that stabilizes the austenite phase, and in the present invention, a content of 17.0% or more is required. If the Mn content is less than 17.0%, a ferrite phase is generated in the weld metal, and the cryogenic impact toughness is significantly reduced. For this reason, the Mn content is set to 17.0% or more. It is preferably set to 18.0% or more, and more preferably set to 19.0% or more. On the other hand, if the Mn content exceeds 30.0%, excessive Mn segregation occurs during solidification, inducing hot cracking. For this reason, the Mn content is set to 30.0% or less. It is preferably set to 28.0% or less, and more preferably set to 27.0% or less.
[0042] [P:0.030% or less] P is an element that segregates at grain boundaries and induces hot cracking, and in the present invention, it is preferable to reduce it as much as possible, but 0.030% or less is acceptable. Therefore, the P content is set to 0.030% or less. It is preferably 0.020% or less, more preferably 0.018% or less, even more preferably 0.016% or less, and most preferably 0.014% or less. Note that excessive reduction leads to an increase in refining costs. Therefore, the P content is preferably adjusted to 0.002% or more.
[0043] [S:0.030% or less] S exists as sulfide-based inclusions MnS in the weld metal. MnS acts as a fracture initiation point, and therefore reduces cryogenic impact toughness. Therefore, the S content is set to 0.030% or less. It is preferably set to 0.025% or less, more preferably set to 0.020% or less, and further preferably set to 0.017% or less. However, excessive reduction of the S content leads to an increase in refining costs. Therefore, it is preferable to adjust the S content to 0.001% or more.
[0044] [Al: 0.001%~0.100%] Al acts as a deoxidizer, increases the viscosity of the molten metal, and has an important effect of stably maintaining the bead shape. In addition, Al narrows the temperature range of the solid-liquid coexistence region of the molten metal, and contributes to suppressing the occurrence of hot cracks in the weld metal. Since such effects become prominent when the Al content is 0.001% or more, the Al content is set to 0.001% or more. It is preferably 0.005% or more, and more preferably 0.010% or more. On the other hand, when it is contained in excess of 0.100%, the viscosity of the molten metal becomes too high, and conversely, the bead does not spread, and defects such as poor fusion increase. Therefore, the Al content is set to 0.100% or less. It is preferably 0.060% or less, more preferably 0.050% or less, and even more preferably 0.040% or less.
[0045] [Cr: 0.4%~5.5%] Cr acts as an element that stabilizes the austenite phase at cryogenic temperatures, and has the effect of improving the cryogenic fracture toughness of the weld metal. It also has the effect of improving the strength of the weld metal, the effect of increasing the liquidus temperature of the molten metal to prevent hot cracking of the weld metal during welding, and the effect of improving the corrosion resistance of the weld metal. If the Cr content is too low, these effects cannot be obtained. To achieve such effects, it is necessary to contain 0.4% or more. It is preferably 0.6% or more, and more preferably 0.8% or more. On the other hand, if the Cr content is too high, Cr carbides are precipitated in the weld metal, which reduces the cryogenic fracture toughness of the weld metal, so it is necessary to keep it at 5.5% or less. It is preferably 5.0% or less, and more preferably 4.5% or less.
[0046] [Mo: 0.01%~3.50%] Mo is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve the strength of the weld metal. It also has the effect of improving the strength of the weld metal by solid solution strengthening. In order to achieve this effect, the Mo content must be 0.01% or more. It is preferably 0.30% or more, more preferably 0.50% or more, and even more preferably 1.00% or more. On the other hand, if it is contained in excess of 3.50%, it precipitates as carbides and becomes the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, the Mo content is set to 3.50% or less. It is preferably 3.20% or less, more preferably 3.00% or less, and even more preferably 2.50% or less.
[0047] [Ni:0.01%~10.00%] Ni is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve cryogenic impact toughness. Ni also has the effect of stabilizing the austenite phase, so if the Ni content is further increased, the austenite phase is stabilized and the cryogenic impact toughness of the weld metal is improved. In order to achieve this effect, the Ni content must be 0.01% or more. It is preferably 0.02% or more, more preferably 0.05% or more, and even more preferably 1.00% or more. On the other hand, Ni is an expensive element, and a content exceeding 10.00% is economically disadvantageous. Therefore, the Ni content is set to 10.00% or less. It is preferably 8.00% or less, more preferably 7.00% or less, even more preferably 6.50% or less, and most preferably 6.00% or less.
[0048] [N:0.0200%~0.1500%] N is an element that is inevitably mixed, but is intentionally mixed in the present invention. Like C, N effectively contributes to improving the strength of the weld metal, stabilizes the austenite phase, and contributes to a stable improvement in cryogenic impact toughness. Furthermore, when the content of N is increased, it has the effect of narrowing the solid-liquid coexistence temperature range, and is an additive element that suppresses the occurrence of hot cracking in high Mn steel. Such an effect becomes remarkable when the content is 0.0200% or more. Therefore, the N content is set to 0.0200% or more. It is preferably 0.0500% or more, more preferably 0.0800% or more, and even more preferably 0.1000% or more. On the other hand, when it is contained in excess of 0.1500%, nitrides are formed, low-temperature toughness is reduced, and the amount of solid-solubilized N becomes too large, causing welding defects such as blowholes and pits. Therefore, N is set to 0.1500% or less. It is preferably 0.1400% or less, and more preferably 0.1300% or less.
[0049] As a method for adding N to the weld metal, as described below, it is possible to add N by mixing nitrogen gas with the shielding gas used during gas metal arc welding, or to add N by increasing the N content in the solid wire, which is the welding material.
[0050] [Optional composition of weld metal] The weld metal of the present invention has the basic chemical composition described above, but in addition to this chemical composition, it may contain one or more optional components selected from V: 0.01%-1.00%, Ti: 0.010%-1.000%, Nb: 0.010%-1.000%, W: 0.01%-1.00%, Cu: 0.01%-1.00%, and B: 0.0015% or less, as required. The reasons for limiting each of the compositions are as follows.
[0051] [V:0.01%~1.00%] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. In order to obtain such an effect, when V is contained, it is preferable that the V content be 0.01% or more. More preferably, it is 0.02% or more. On the other hand, when the V content exceeds 1.00%, the carbides become coarse and become the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, when V is contained, it is preferable that the V content be 1.00% or less. More preferably, it is 0.80% or less, and even more preferably, it is 0.60% or less.
[0052] [Ti: 0.010%~1.000%] Ti is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. Ti also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, Ti is preferably contained at 0.010% or more. More preferably, it is 0.015% or more. On the other hand, if Ti is contained at more than 1.000%, the carbides become coarse and become the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, the Ti content is preferably 1.000% or less. More preferably, it is 0.800% or less, and even more preferably, it is 0.600% or less.
[0053] [Nb: 0.010%~1.000%] Nb is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating carbides. Nb also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, the Nb content is preferably 0.010% or more. More preferably, it is 0.015% or more. On the other hand, if the Nb content exceeds 1.000%, the carbides become coarse and become the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, the Nb content is preferably 1.000% or less. More preferably, it is 0.800% or less, even more preferably, it is 0.700% or less, and most preferably, it is 0.600% or less.
[0054] [W:0.01%~1.00%] W is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating carbides, and further contributes to stabilizing the austenite phase and improving the cryogenic impact toughness. W also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, it is preferable that W is contained at 0.01% or more. More preferably, it is 0.02% or more, and even more preferably, it is 0.05% or more. On the other hand, if W exceeds 1.00%, the carbides become coarse and become the starting point of fracture, resulting in a decrease in the cryogenic impact toughness. Therefore, the W content is preferably 1.00% or less. More preferably, it is 0.80% or less, and even more preferably, it is 0.60% or less.
[0055] [Cu:0.01%~1.00%] Cu is an element that stabilizes the austenite phase, and stabilizes the austenite phase even at cryogenic temperatures, thereby improving the cryogenic impact toughness of the weld metal. In order to obtain such an effect, the Cu content is preferably 0.01% or more, and more preferably 0.04% or more. On the other hand, if a large amount of Cu is contained, exceeding 1.00%, it segregates during solidification and induces hot cracking during welding. Therefore, the Cu content is preferably 1.00% or less, and more preferably 0.80% or less.
[0056] [B:0.0015% or less] B is an element that segregates at grain boundaries and contributes to improving the toughness of steel materials, but if it is contained in excess of 0.0015%, coarse nitrides and carbides increase, decreasing toughness. For this reason, the B content is preferably 0.0015% or less, more preferably 0.0010% or less, and even more preferably 0.0007% or less.
[0057] [Remainder of weld metal composition] The balance other than the above chemical composition is composed of Fe and inevitable impurities. Examples of inevitable impurities include H, O, Mg, Ca, Zn, Re, and REM, and a total of 0.0100% or less is acceptable. In addition, as long as the above basic composition and optional composition are satisfied, elements other than these may be contained, and such embodiments are also included in the technical scope of the present invention.
[0058] The chemical composition of the weld metal is determined mainly by the inflow ratio of the base metal and the welding material such as the gas metal arc welding wire.
[0059] [Welding method and conditions] Next, specific examples of welding conditions and the like for a gas metal arc welding method suitable for producing the welded joint of the present invention will be described. An example of a cross section of a welded metal part of a welded joint is shown in Fig. 1. The plate thickness t of the steel material serving as the base material 1 is 5 mm to 102 mm.
[0060] When preparing a test piece to be described later, the base materials 1 are butted together to form a V-groove with a groove angle θ of 35° to 60° in accordance with JIS Z 3111. A solid wire with a diameter of 1.0 mm to 1.6 mm can be used as an electrode for gas metal arc welding. Preheating is not required.
[0061] Other welding conditions are current: 180A to 300A (DCEP), voltage: 20V to 30V, welding speed: 10cm / min to 25cm / min, and welding heat input: 16.0kJ / cm to 50.0kJ / cm. Here, if the current is less than 180A, the wire cannot be sufficiently melted and the arc becomes unstable, and if it exceeds 300A, the transfer of the droplets becomes unstable and a large amount of spatter occurs. Also, if the welding heat input is less than 16.0kJ / cm, the input heat is low, the base metal and the weld metal do not fuse properly, and a humping bead occurs, and if it exceeds 50.0kJ / cm, the bead shape becomes irregular. More preferably, it is 18.0kJ / cm to 28.0kJ / cm. Even more preferably, it is 20.0kJ / cm to 22.0kJ / cm. Also, it is preferable that the interpass temperature is 150°C or less.
[0062] Examples of welding positions include downward, horizontal, upward, and vertical upward welding. The groove shape may be a V groove as shown in Fig. 1, a L groove, a K groove, an X groove, etc. As described above, the groove angle θ is preferably 35° to 60°, and more preferably 40° to 55°.
[0063] Under the above-mentioned welding conditions, a weld metal 2 is formed in the V-groove by single-layer or multi-layer welding, and the weld metal 2 has a form in which multiple layers of weld metal 3 are stacked up. Note that if the welding method (welding conditions) of the present invention are not followed, welding defects such as hot cracks 4 will occur in part of the weld metal layer 3, but in the welding method of the present invention, such welding defects such as hot cracks 4 will not occur.
[0064] [Shielding gas] In the present invention, as the shielding gas for gas metal arc welding, a shielding gas containing [A], by volume, 1.0% or more and less than 30.0% nitrogen (N2) gas, with the remainder being carbon dioxide gas and unavoidable impurities, is used. Alternatively, a shielding gas containing [B], by volume, 1.0% or more and less than 30.0% nitrogen gas and 56.0% or more and less than 79.2% Ar gas, with the remainder being carbon dioxide gas and unavoidable impurities, is used. Either [A] or [B] above may be selected and used. In the following, "%" in the gas component content means "volume %".
[0065] The nitrogen in the shielding gas is an element that, when dissolved in the weld metal of high Mn steel, improves the strength of the weld metal and the welded joint by solid solution strengthening. Furthermore, increasing the N content in the weld metal shows a tendency to reduce the solid-liquid coexistence temperature range, improving hot cracking susceptibility. In order to obtain such an effect, it is necessary to contain 1.0% or more of nitrogen in the shielding gas. Therefore, the nitrogen content in the shielding gas is set to 1.0% or more. It is preferably 5.0% or more, and more preferably 10.0% or more. On the other hand, if the nitrogen content in the shielding gas is 30.0% or more, the arc becomes unstable, and a large number of welding defects such as blowholes and pits occur, deteriorating the joint characteristics. Therefore, the nitrogen content in the shielding gas is set to less than 30.0%. It is preferably 25.0% or less, and more preferably 20.0% or less.
[0066] Next, we will explain carbon dioxide (CO2) gas, which is the remaining part of the shielding gas. Carbon dioxide gas is the most commonly used shielding gas, and is characterized by its low cost compared to Ar gas and its deep penetration.
[0067] The carbon dioxide gas is used as the remaining gas in the shielding gas [A] described above. In this case, the carbon dioxide gas content is the remainder excluding the nitrogen gas content (1.0% or more and less than 30.0%), and the carbon dioxide gas content is more than 70.0% and 99.0% or less.
[0068] In contrast, like the shielding gas [B] described above, carbon dioxide gas may be used not only alone but also mixed with Ar gas, which is an inert gas. When using this mixed gas [B], it is preferable to use a gas in which Ar gas:carbon dioxide gas is mixed at a ratio of 4:1, which is generally easy to obtain. Therefore, the content of components other than nitrogen gas in the mixed gas [B] is also more than 70.0% and less than 99.0%, so the respective contents of Ar gas and carbon dioxide gas are Ar gas of 56.0% or more and less than 79.2%, and carbon dioxide gas of more than 14.0% and less than 19.8%.
[0069] In addition, the unavoidable impurities are gases other than nitrogen gas, carbon dioxide gas, and Ar gas, and examples thereof include oxygen (O2) gas, hydrogen (H2) gas, and the like.
[0070] The flow rate of the shielding gas is preferably 10 L / min to 30 L / min, and more preferably 15 L / min to 25 L / min.
[0071] As described above, by using a shielding gas containing nitrogen gas in an amount of 1.0% or more and less than 30.0% by volume, the N content in the weld metal becomes 0.0200% to 0.1500%, N dissolves in the weld metal, and the strength of the weld metal and welded joint can be improved.
[0072] [Basic composition of solid wire] The present invention relates to a welded joint in which the above-mentioned high Mn steels are welded together by a gas metal arc welding method to form a weld metal part consisting of a single layer or multiple layers of weld metal. The solid wire used in this case has a preferred chemical composition as shown below. In the following, "%" in the "chemical composition" of the solid wire means "mass %".
[0073] A preferred basic composition for the solid wire used in the present invention contains N: 0.4000% or less. A more preferred basic composition is as follows: C: 0.20% to 0.80%, Si: 0.15% to 1.00%, Mn: 17.0% to 28.0%, P: 0.030% or less, S: 0.030% or less, Ni: 0.01% to 10.00%, Cr: 0.4% to 4.0%, and Mo: 0.01% to 3.50%. Furthermore, it contains less than 0.0015% B, with the balance being Fe and unavoidable impurities. The reasons for limiting each chemical composition are as follows.
[0074] [N:0.4000% or less] In order to increase the N content in the weld metal, when a conventional shielding gas made of carbon dioxide gas or a mixture of carbon dioxide gas and argon gas is used, the N content in the weld metal does not increase, so it is preferable to use a wire with an increased N content. In this case, the N content of the wire is preferably 0.4000% or less. If the N content of the wire exceeds 0.4000%, the amount of N added to the weld metal becomes excessive, and the intragranular strength becomes excessively strong compared to the grain boundary strength, so that fracture occurs from the grain boundary and the cryogenic impact toughness may deteriorate. Therefore, when a conventional shielding gas made of carbon dioxide gas or a mixture of carbon dioxide gas and argon gas is used as the shielding gas, the N content is preferably 0.4000% or less. More preferably, it is 0.3800% or less, and even more preferably, it is 0.3600% or less.
[0075] However, in the case of the method of adding N to the weld metal from nitrogen gas by using a gas containing 1.0% or more but less than 30.0% nitrogen gas by volume as the shielding gas described above, if the N content of the wire is high, the N content in the weld metal becomes excessive, and the cryogenic impact toughness deteriorates. For this reason, it is preferable to keep the N content of the wire to 0.1200% or less. More preferably, it is 0.1100% or less, and even more preferably, it is 0.1000% or less.
[0076] N is an element that effectively contributes to improving the intragranular strength of the weld metal, stabilizes the austenite phase, and contributes to a stable improvement in cryogenic impact toughness. To obtain such effects, the N content is preferably 0.0030% or more, more preferably 0.0040% or more, and even more preferably 0.0060% or more.
[0077] [C:0.20%~0.80%] C is an element that has the effect of increasing the strength of the weld metal by solid solution strengthening, and C is also an inexpensive and important element that has the effect of stabilizing the austenite phase and improving the cryogenic impact toughness of the weld metal. In order to obtain such effects, the C content is preferably 0.20% or more. More preferably, it is 0.25% or more, and even more preferably, it is 0.28% or more. On the other hand, if it is contained in excess of 0.80%, carbides are excessively generated in the weld metal, the cryogenic impact toughness decreases, and further, hot cracking during welding may easily occur. Therefore, the C content is preferably 0.80% or less. More preferably, it is 0.75% or less, even more preferably, it is 0.70% or less, and most preferably, it is 0.63% or less.
[0078] [Si:0.15%~1.00%] Si acts as a deoxidizer, increases the yield of Mn, increases the viscosity of the molten metal, and has the effect of stably maintaining the bead shape. In order to obtain such an effect, the Si content is preferably 0.15% or more. More preferably, it is 0.18% or more, even more preferably, it is 0.20% or more, and most preferably, it is 0.25% or more. On the other hand, if it is contained in excess of 1.00%, it may reduce the cryogenic impact toughness of the weld metal, and may also segregate during solidification, generating a liquid phase at the solidification cell interface, thereby deteriorating the hot cracking resistance. Therefore, the Si content is preferably 0.90% or less. More preferably, it is 0.80% or less, even more preferably, it is 0.75% or less, and most preferably, it is 0.70% or less.
[0079] [Mn: 17.0%~28.0%] Mn is an inexpensive element that has the effect of stabilizing the austenite phase, but if the Mn content is less than 17.0%, a ferrite phase is generated in the weld metal, and the cryogenic impact toughness may be significantly reduced. For this reason, the Mn content is preferably 17.0% or more. More preferably, it is 18.0% or more, and even more preferably, it is 18.5% or more. On the other hand, if the Mn content exceeds 28.0%, the stacking fault energy increases and the resistance during deformation decreases, so that the strength may decrease. For this reason, the Mn content is preferably 28.0% or less. More preferably, it is 27.0% or less, and even more preferably, it is 26.0% or less.
[0080] [P:0.030% or less] P is an element that segregates at grain boundaries and induces hot cracking. In the present invention, it is preferable to reduce the P content as much as possible, but 0.030% or less is acceptable. Therefore, the P content is preferably 0.030% or less. More preferably, it is 0.020% or less, even more preferably, it is 0.018% or less, and most preferably, it is 0.014% or less. On the other hand, in order to extremely reduce the P content to less than 0.002%, a long refining time is required, and the refining cost rises. Therefore, from an economical point of view, the P content is preferably 0.002% or more.
[0081] [S:0.030% or less] S exists as sulfide-based inclusions MnS in the weld metal. MnS can be the starting point of fracture, and can reduce the cryogenic impact toughness. Therefore, the S content is preferably 0.030% or less, more preferably 0.025% or less, even more preferably 0.020% or less, and most preferably 0.017% or less. On the other hand, excessive reduction leads to an increase in refining costs. Therefore, the S content is preferably 0.001% or more.
[0082] [Ni:0.01%~10.00%] Ni is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve cryogenic impact toughness. Ni also has the effect of stabilizing the austenite phase, so if the Ni content is further increased, the austenite phase is stabilized and the cryogenic impact toughness of the weld metal is improved. In order to obtain such an effect, the Ni content is preferably 0.01% or more, and more preferably 1.00% or more. On the other hand, Ni is an expensive element, and a content exceeding 10.00% is economically disadvantageous. Therefore, the Ni content is preferably 10.00% or less, and more preferably 8.00% or less, further preferably 7.00% or less, and most preferably 6.00% or less.
[0083] [Cr:0.4%~4.0%] Cr is an element that stabilizes the austenite phase at cryogenic temperatures and effectively contributes to improving cryogenic impact toughness and weld metal strength. Cr also narrows the temperature range of the solid-liquid coexistence region of the molten metal and effectively acts to suppress the occurrence of hot cracks. In order to obtain such effects, the Cr content is preferably 0.4% or more. More preferably, it is 0.8% or more, even more preferably, it is 1.0% or more, and most preferably, it is 1.2% or more. On the other hand, if it is contained in excess of 4.0%, Cr carbides may be formed, which may lead to a decrease in cryogenic impact toughness. Therefore, the Cr content is preferably 4.0% or less. More preferably, it is 3.5% or less, even more preferably, it is 3.2% or less, and most preferably, it is 2.8% or less.
[0084] [Mo: 0.01%~3.50%] Mo is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve the strength of the weld metal. It also has the effect of improving the strength of the weld metal by solid solution strengthening. In order to obtain such an effect, the Mo content is preferably 0.01% or more. More preferably, it is 0.50% or more, even more preferably, it is 1.00% or more, and most preferably, it is 1.50% or more. On the other hand, if it is contained in excess of 3.50%, the effect of increasing the strength of the weld metal becomes limited, and it may precipitate as carbides and become the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, the Mo content is preferably 3.50% or less. More preferably, it is 3.30% or less, even more preferably, it is 3.10% or less, and most preferably, it is 3.00% or less.
[0085] [B: Less than 0.0015%] B is one of the elements that segregate at the austenite grain boundaries. If B is mixed in at 0.0015% or more, it forms boron nitride at the austenite grain boundaries, reducing strength, and the boron nitride may become the starting point of fracture, reducing cryogenic impact toughness. Therefore, the B content is preferably less than 0.0015%. More preferably, it is 0.0010% or less, and even more preferably, it is 0.0005% or less.
[0086] [Optional composition of solid wire] The above-mentioned chemical composition is the basic composition preferred for the wire used in the present invention, but in addition to this basic composition, the wire may contain the following optional compositions as necessary. These are one or more selected from V: 0.01%-0.04%, Ti: 0.01%-0.04%, Nb: 0.01%-0.04%, Cu: 0.01%-1.00%, and Al: 0.002%-0.100%. The reasons for limiting these compositions are as follows.
[0087] [V:0.01%~0.04%] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. To obtain such an effect, the V content is preferably 0.01% or more. On the other hand, if the V content exceeds 0.04%, the carbides become coarse and become the starting point of cracks during wire drawing, which may reduce wire drawing workability and wire manufacturability. Therefore, the V content is preferably 0.04% or less.
[0088] [Ti: 0.01%~0.04%] Ti is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. It also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, the Ti content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the Ti content exceeds 0.04%, the carbides become coarse and become the starting point of cracks during the wire drawing process of the solid wire, which may reduce the wire drawing processability and the manufacturability of the wire. Therefore, the Ti content is preferably 0.04% or less, and more preferably 0.03% or less.
[0089] [Nb: 0.01%~0.04%] Nb is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating carbides. It also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, the Nb content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the Nb content exceeds 0.04%, the carbides become coarse and become the starting point of cracks during the wire drawing process of the solid wire, which may reduce the wire drawing processability and the manufacturability of the wire. Therefore, the Nb content is preferably 0.04% or less, and more preferably 0.03% or less.
[0090] [Cu:0.01%~1.00%] Cu is an element that stabilizes the austenite phase, and stabilizes the austenite phase even at cryogenic temperatures, thereby improving the cryogenic impact toughness of the weld metal. In order to obtain such an effect, the Cu content is preferably 0.01% or more. More preferably, it is 0.10% or more, and even more preferably, it is 0.20% or more. On the other hand, if the Cu content exceeds 1.00%, the hot ductility decreases, and the manufacturability of the wire may decrease. Therefore, the Cu content is preferably 1.00% or less. More preferably, it is 0.70% or less, and even more preferably, it is 0.50% or less.
[0091] [Al: 0.002%~0.100%] Al acts as a deoxidizer, increases the viscosity of the molten metal, stably maintains the bead shape, and has an important effect of reducing the occurrence of spatter. It also increases the liquidus temperature of the molten metal, contributing to suppression of hot cracking of the weld metal. To obtain such effects, the Al content is preferably 0.002% or more. More preferably, it is 0.010% or more, and even more preferably, it is 0.020% or more. On the other hand, if it is contained in excess of 0.100%, the viscosity of the molten metal becomes too high, and conversely, spatter increases, and the bead does not spread, and defects such as poor fusion increase. Therefore, the Al content is preferably 0.100% or less. More preferably, it is 0.060% or less, and even more preferably, it is 0.050% or less.
[0092] [Remainder of solid wire composition] The remaining composition other than the above-mentioned chemical composition is composed of Fe and inevitable impurities. Examples of inevitable impurities include H, O, Mg, Zn, Re, etc., and a total of 0.010% or less is acceptable. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, elements other than these may be contained, and such embodiments are also included in the technical scope of the present invention. EXAMPLES
[0093] The present invention will be further described below with reference to examples. However, the following examples are merely intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention.
[0094] First, a high Mn steel material for cryogenic use (plate thickness: 20 mm) was prepared as a test material, and the composition was shown in Table 1. Molten steel having the composition shown in Table 2 was melted in a vacuum melting furnace and cast to obtain a steel ingot of 100 kg. The obtained steel ingot was heated to 1200°C, hot rolled, and then cold rolled (wire drawing) to obtain a solid wire for gas metal arc welding having a diameter of 1.2 mm.
[0095] The steel materials in Table 1 above were butted together in accordance with JIS Z 3111 to form a 50° V-groove (see FIG. 1). Then, using the solid wire in Table 2 above as the welding material, consumable electrode gas metal arc welding was performed under welding conditions of a current of 200 A to 250 A, a voltage of 24 V to 26 V, a welding speed of 14 cm / min, and a gas flow rate of 20 L / min to obtain a welded joint having a weld metal in the V-groove. Table 3 shows the welding conditions.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Table 3]
[0099] [Weld metal composition analysis] A 5 mm square block was taken from the center of the plate thickness and the center of the weld line in the weld metal of the welded joint, and the content of each component in the weld metal was measured using the inert gas fusion-thermal conductivity method. The N content was the total amount of N in the weld metal. The results are shown in Table 4.
[0100] [Table 4]
[0101] [Evaluation of hot crack resistance] After welding, a 10 mm thick macro test piece was taken from the center position in the weld line direction with a microcutter, with the observation surface being a cross section perpendicular to the weld line, and the cross section of the weld metal was observed with an optical microscope (30x) to determine the presence or absence of hot cracking. Hot cracking was determined to have occurred if an opening was observed in the structure photograph taken with the optical microscope. If hot cracking was observed, it was rated as "present." If hot cracking was not observed, it was rated as "absent."
[0102] [Mechanical properties of weld metal] Tensile test pieces (parallel portion diameter 6 mmΦ) and Charpy impact test pieces (V notch) were taken from the obtained weld metal in accordance with the provisions of JIS Z 3111, and tensile tests and impact tests were performed. The positions from which the test pieces (V notch) were taken are shown in Figure 2. The direction of the V notch 8 of the test piece 6 was perpendicular to the surface of the base metal 1. The test piece 6 was taken so that the center line 7 of the test piece 6 passed through the midpoint (1 / 2t) of the plate thickness t of the base metal 1, and the position of the V notch 8 was the midpoint between the fusion lines 5 of the weld metal 2 (the center of the weld metal).
[0103] Tensile tests were performed on three wires at room temperature, and the average of the obtained values (0.2% yield strength) was regarded as the tensile properties of the weld metal using the wire. Here, weld metals that showed an average improvement of 20 MPa or more in yield stress (0.2% yield strength) and tensile strength at room temperature (25°C) due to differences in shielding gas type were evaluated as having good mechanical properties.
[0104] In addition, Charpy impact tests were performed on three specimens each, and the absorbed energy ( V E -196) was obtained, and the average value was regarded as the cryogenic impact toughness of the weld metal using the wire. A weld metal having an absorbed energy of 28 J or more in a Charpy impact test at -196°C was evaluated as having excellent cryogenic impact toughness.
[0105] The results obtained are shown in Table 5.
[0106] [Table 5]
[0107] All of the welded joints produced in the examples of the present invention were welded joints that did not suffer from hot cracking during welding and had excellent hot cracking resistance. Compared to conventional gas metal arc welded joints that use carbon dioxide or a mixture of carbon dioxide and argon gas as the shielding gas, the 0.2% proof stress and tensile strength were improved by an average of 20 MPa or more when nitrogen gas was mixed into the shielding gas or the N content of the wire was increased.
[0108] As comparative examples, the characteristics of joints produced by general gas metal arc welding, which does not contain nitrogen gas in the shielding gas, are shown for joints Nos. 1, 6, 11, 13, 15, 18, 20, and 23.
[0109] All of the welded joints produced in the examples of the present invention were welded joints that did not suffer from hot cracking during welding and had excellent hot cracking resistance. Compared to general gas metal arc welded joints that do not contain nitrogen gas in the shielding gas, the yield stress (0.2% proof stress) and tensile strength of the weld metal at room temperature (25°C) were improved by an average of 20 MPa or more. In addition, excellent cryogenic impact toughness was also obtained.
[0110] Here, the difference in 0.2% proof stress and tensile strength between welded joints produced using shielding gas containing no nitrogen gas and shielding gas containing nitrogen gas (average improvement of 20 MPa or more) will be further explained based on the data in Table 5. For example, joints No. 1 to 5 in Table 5 are all joints produced using No. a steel material and No. A wire. However, the type of shielding gas is carbon dioxide gas alone without nitrogen gas in joint No. 1, and gas containing 10% to 40% by volume of nitrogen gas in joint No. 2 to 5. When the weld metal properties of the obtained joints were examined, the 0.2% proof stress of joint No. 1 (without nitrogen gas) was 403 MPa, while that of joint No. 2 (containing 10% by volume of nitrogen gas) was 441 MPa, a difference of 38 MPa. In addition, the tensile strength of joint No. 1 was 778 MPa, while that of joint No. 2 was 803 MPa, a difference of 25 MPa. Furthermore, in the case of joint No. 3 (containing 20% nitrogen gas by volume), the 0.2% proof stress was 460 MPa, and the difference with joint No. 1 was 57 MPa. The tensile strength was 819 MPa, and the difference with joint No. 1 was 41 MPa. Similarly, in the case of joint No. 4 (containing 30% nitrogen gas by volume), the difference in 0.2% proof stress was 82 MPa, and the difference in tensile strength was 52 MPa. In the case of joint No. 5 (containing 40% nitrogen gas by volume), the difference in 0.2% proof stress was 101 MPa, and the difference in tensile strength was 57 MPa. As described above, when nitrogen gas was added to the shielding gas, the tensile strength and 0.2% proof stress improved according to the nitrogen gas content.
[0111] In addition, joints No. 4, 5, 9, 10, and 17 had excessive nitrogen gas content in the shielding gas, which resulted in numerous pits and blowholes, making them unsuitable as welded joints.
[0112] Furthermore, joints No. 18 and 19 are examples of welded joints made of steel No. d having a chemical composition outside the range specified in the present invention and solid wire No. E having a chemical composition outside the preferred range, which are used in the welding method according to the present invention. In joint No. 18, nitrogen gas is not contained in the shielding gas, so it does not reach the 0.2% yield strength that is preferred in the present invention. However, it was found that when nitrogen gas is contained in the shielding gas as in joint No. 19, the N content in the weld metal increases, as in the other examples, and the effect of improving strength can be obtained.
[0113] In comparison with joint No. 23, which was made by gas metal arc welding without containing nitrogen gas in the shielding gas, joint No. 24, which used wire No. F with the same composition but increased N content (0.3290%), had a N content in the weld metal within the range specified by the present invention even though the shielding gas did not contain nitrogen gas, and the difference in 0.2% proof stress was 59 MPa and the difference in tensile strength was 37 MPa. Furthermore, joints No. 25 and No. 26, which used shielding gases containing 20% and 40% nitrogen gas, respectively, had blowholes because the N content in the weld metal exceeded the upper limit of the specified range, making them unsuitable joints.
[0114] [Relationship between the nitrogen content of shielding gas or the N content of wire and the strength of weld metal] Based on the data in Table 5 above, the changes in 0.2% proof stress and tensile strength versus N content in the weld metal were organized for the methods of adding N by mixing nitrogen gas into the shielding gas and by increasing the N content in the wire.
[0115] Fig. 3 is a diagram showing the change in 0.2% proof stress versus N content in the weld metal with a change in nitrogen gas content, and Fig. 4 is a diagram showing the change in tensile strength versus N content in the weld metal with a change in nitrogen gas content. Fig. 5 is a diagram showing the change in 0.2% proof stress versus N content in the weld metal with a change in N content in the wire, and Fig. 6 is a diagram showing the change in tensile strength versus N content in the weld metal with a change in N content in the wire. Here, Figs. 3 and 4 are grouped according to the nitrogen content of the shielding gas, and Figs. 5 and 6 are grouped according to the high and low N content of the wire.
[0116] As can be seen from Fig. 3, when the nitrogen gas content in the shielding gas is changed for the same steel material and the same wire combination, the 0.2% proof stress is higher when the nitrogen gas content is 10% by volume than when there is no nitrogen gas, and is even higher when the nitrogen gas content is 20% by volume. In the case of the tensile strength in Fig. 4, the tensile strength increases as the nitrogen content increases to 10% by volume and then to 20% by volume. Similarly, Figs. 5 and 6 show that as the N content of the wire increases, the N content in the weld metal increases, thereby improving the strength. From these results, it was confirmed that increasing the N content in the weld metal of the present invention is effective in improving the strength of the weld metal. [Explanation of symbols]
[0117] 1 Base material (steel material) 2. Weld metal 3. Weld metal layer 4. Hot cracking 5. Melting Line 6 Test specimens 7. Center line of test piece 8 V-notch position t Plate thickness
Claims
1. A gas metal arc welded joint of steel material formed by forming a weld metal using a shielding gas and a solid wire, The steel material is a high Mn-containing austenitic steel, The chemical composition of the steel material is, in mass%, C: 0.10% to 0.70%, Si: 0.05% to 1.00%, Mn: 18.0% to 30.0%, P: 0.030% or less, S: 0.007% or less, Al: 0.010% to 0.070%, Cr: 2.50% to 7.00%, N: 0.0050% to 0.0500%, O (oxygen): 0.0050% or less The balance is Fe and unavoidable impurities. The chemical composition of the weld metal is, in mass%, C: 0.15% to 0.80%, Si: 0.10% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Al: 0.001% to 0.100%, Cr: 0.4% to 5.5%, Mo: 0.01% to 3.50%, Ni: 0.01% to 10.00%, N: 0.0200% to 0.1500% The balance is Fe and unavoidable impurities.
1. A gas metal arc welded joint comprising:
2. The chemical composition of the steel further comprises, in mass%, Mo: 0.01% to 2.00%, V: 0.01% to 2.00%, W: 0.01% to 2.00%, Ni: 0.01% to 4.00%, REM: 0.0010% to 0.0200%; B: 0.0003% to 0.0030% Contains one or more selected from the following:
2. The gas metal arc welded joint of claim 1.
3. The chemical composition of the weld metal further comprises, in mass %, V: 0.01% to 1.00%, Ti: 0.010% to 1.000%, Nb: 0.010% to 1.000%, W: 0.01% to 1.00%, Cu: 0.01% to 1.00% and B: 0.0015% or less Contains one or more selected from the following:
3. A gas metal arc welded joint according to claim 1 or 2.
4. 3. A gas metal arc welded joint according to claim 1, wherein the shielding gas is any one of the following gases [A] and [B]. [A] A gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas, with the remainder being carbon dioxide gas and unavoidable impurities. [B] A gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas and 56.0% or more and less than 79.2% Ar gas, with the remainder being carbon dioxide gas and unavoidable impurities.
5. 4. A gas metal arc welded joint according to claim 3, wherein the shielding gas is any one of the following gases [A] and [B]. [A] A gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas, with the remainder being carbon dioxide gas and unavoidable impurities. [B] A gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas and 56.0% or more and less than 79.2% Ar gas, with the remainder being carbon dioxide gas and unavoidable impurities.
6. 3. The gas metal arc welded joint according to claim 1, wherein the N content of the solid wire is 0.4000% or less, in mass percent.
7. 4. The gas metal arc welded joint according to claim 3, wherein the N content of the solid wire is 0.4000% or less, in mass percent.
8. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 3. The gas metal arc welded joint according to claim 1, wherein the weld strength is 28 J or more.
9. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 4. The gas metal arc welded joint according to claim 3, wherein the weld strength is 28 J or more.
10. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 5. The gas metal arc welded joint according to claim 4, characterized in that the weld strength is 28 J or more.
11. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 6. The gas metal arc welded joint according to claim 5, characterized in that the weld strength is 28 J or more.
12. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 7. The gas metal arc welded joint according to claim 6, wherein the weld strength is 28 J or more.
13. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 8. The gas metal arc welded joint according to claim 7, characterized in that the weld strength is 28 J or more.
Citation Information
Patent Citations
High-strength welded joints with excellent cryogenic impact toughness and wires for flux-cored arc welding therefor
JP2017502842A
In-situ girth welding technique for high manganese steel slurry pipelines.
JP2022081631A
Method for producing high-strength welded joint for cryogenic environments
WO2020203335A1
Solid wire for gas metal arc welding and gas metal arc welding method
WO2020203336A1
Solid wire for gas metal arc welding use
WO2022030200A1